Typing of urinary JC virus DNA offers a novel means of tracing human migrations - Sugimoto, Chie (The National Academy of Sciences of the USA, 1997)
Although polyomavirus JC (JCV) is the proven pathogen of progressive multifocal leukoencephalopathy, the fatal demyelinating disease, this virus is ubiquitous as a usually harmless symbiote among human beings. JCV propagates in the adult kidney and excretes its progeny in urine, from which JCV DNA can readily be recovered. The main mode of transmission of JCV is from parents to children through long cohabitation. In this study, we collected a substantial number of urine samples from native inhabitants of 34 countries in Europe, Africa, and Asia. A 610-bp segment of JCV DNA was amplified from each urine sample, and its DNA sequence was determined. A worldwide phylogenetic tree subsequently constructed revealed the presence of nine subtypes including minor ones. Five subtypes (EU, Af2, B1, SC, and CY) occupied rather large territories that overlapped with each other at their boundaries. The entire Europe, northern Africa, and western Asia were the domain of EU, whereas the domain of Af2 included nearly all of Africa and southwestern Asia all the way to the northeastern edge of India. Partially overlapping domains in Asia were occupied by subtypes B1, SC, and CY. Of particular interest was the recovery of JCV subtypes in a pocket or pockets that were separated by great geographic distances from the main domains of those subtypes. Certain of these pockets can readily be explained by recent migrations of human populations carrying these subtypes. Overall, it appears that JCV genotyping promises to reveal previously unknown human migration routes: ancient as well as recent.